Correlation between bulk characteristics of aggregated β-lactoglobulin and its surface and foaming properties. (December 2016) - Dombrowski, Jannika; Johler, Florian; Warncke, Malou; Kulozik, Ulrich
Abstract: Bovine β-lactoglobulin features a pronounced surface activity, and therefore, is widely applied in order to provide stability to food-related aerated systems. Due to its distinct tertiary and quaternary structure, it can be used both in native state as well as in the form of thermally aggregated particles. In this context, heat treatment (80 °C/90 min) of highly purified solutions of β-lactoglobulin (c = 10.0 g L − 1 ) under variation of solution pH (6.8 or 8.0) and NaCl concentration (0–130 mM) resulted in the formation of soluble aggregates, whose median particle diameters ranged from about 2.5 nm to 1.1 μm. These differences in particle size in combination with differences in particle characteristics (e.g. surface hydrophobicity, zeta potential) had a significant impact on surface properties, i.e. surface tension, dynamics of protein adsorption and interfacial dilatational properties. Thereby, diffusion rates decreased with increasing median particle diameter. Initial protein adsorption was majorly influenced by surface hydrophobicity. However, reverse observations emerged in terms of foam characteristics. Foam stability clearly increased with increasing aggregate size, showing maxima for the largest particles examined. The increasing foam stabilization ability was also reflected in time-resolved bubble properties, e.g. lower mean bubble areas as well as higher bubble counts for larger aggregates. This observation was traced back to the increasing surface hydrophobicity as well as more negative zeta potential of the aggregates with increasing particle diameter. As a result, sterically stabilized and more impermeable surface films in combination with electrostatic repulsive forces led to a reduction in coalescence rate as indicated by a lower coarsening exponent, and thus, a decrease of foam decay. Graphical abstract: Highlights: Multiscale analysis of β-lactoglobulin aggregates covering a broad size range. Surface hydrophobicity determines initial adsorption to the air/water interface. Particle size and zeta potential determine quasi-equilibrium surface pressure. Highest foam stabilities correlated with maxima in surface elasticity moduli. Increased particle size, hydrophobicity and zeta potential increased foam life time.